Calculation of elastic integral and differential collision cross-sections for low energy Ne+, Ar+, Kr+ and Xe+ ions with neutral He atoms - Barata, J. A. S. (2004)
http://www.sciencedirect.com/science/article/B6TVT-4CJV8FD-2/1/ca6fcda4998b56a276acc3c13ed660de